Design paper of the “Blood pressure targets in post-resuscitation care and bedside monitoring of cerebral energy state: a randomized clinical trial” - Mölström, Simon (Trials, 2019)
BACKGROUND: Neurological injuries remain the leading cause of death in comatose patients resuscitated from out-of-hospital cardiac arrest (OHCA). Adequate blood pressure is of paramount importance to optimize cerebral perfusion and to minimize secondary brain injury. Markers measuring global cerebral ischemia caused by cardiac arrest and consecutive resuscitation and reflecting the metabolic variations after successful resuscitation are needed to assist a more individualized post-resuscitation care. Currently, no technique is available for bedside evaluation of global cerebral energy state, and until now blood pressure targets have been based on limited clinical evidence. Recent experimental and clinical studies indicate that it might be possible to evaluate cerebral oxidative metabolism from measuring the lactate-to-pyruvate (LP) ratio of the draining venous blood. In this study, jugular bulb microdialysis and immediate bedside biochemical analysis are introduced as new diagnostic tools to evaluate the effect of higher mean arterial blood pressure on global cerebral metabolism and the degree of cellular damage after OHCA. METHODS/DESIGN: This is a single-center, randomized, double-blinded, superiority trial. Sixty unconscious patients with sustained return of spontaneous circulation after OHCA will be randomly assigned in a one-to-one fashion to low (63 mm Hg) or high (77 mm Hg) mean arterial blood pressure target. The primary end-point will be a difference in mean LP ratio within 48 h between blood pressure groups. Secondary end-points are (1) association between LP ratio and all-cause intensive care unit (ICU) mortality and (2) association between LP ratio and survival to hospital discharge with poor neurological function. DISCUSSION: Markers measuring cerebral ischemia caused by cardiac arrest and consecutive resuscitation and reflecting the metabolic changes after successful resuscitation are urgently needed to enable a more personalized post-resuscitation care and prognostication. Jugular bulb microdialysis may provide a reliable global estimate of cerebral metabolic state and can be implemented as an entirely new and less invasive diagnostic tool for ICU patients after OHCA and has implications for early prognosis and treatment. TRIAL REGISTRATION: ClinicalTrials.gov (ClinicalTrials.gov Identifier: NCT03095742). Registered March 30, 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-019-3397-1) contains supplementary material, which is available to authorized users.